The Fisherman's Fishing Pole - Wilder, Sterling (East Carolina University, 2017)
While fishing, many fishermen believe that keeping up with a tackle box can be an unnecessary burden. While tackle boxes have the ability to store many lures, they can be heavy, expensive, disorganized, and get in the way. In addition, most fishermen will only use a few lures in a single fishing trip, so why keep up with a cumbersome tackle box? The objective of this project is to design and build a fishing rod that allows for adequate and convenient storage of fishing tackle within the rod itself.
Keywords: Fishing Pole; Lure; Storage